2018
DOI: 10.1039/c8fo00603b
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and immunomodulatory activity of a novel polysaccharide fromFicus carica

Abstract: A novel polysaccharide (FCPW80-2) with a molecular weight of 1.21 × 105 Da was first isolated from Ficus carica through hot water extraction and several chromatographic methods. The structure of FCPW80-2 was determined by chemical and instrumental analysis. The results showed that the backbone of FCPW80-2 consists of (1→5)-linked α-l-Ara, (1→3,6)-linked β-d-Man and (1→4,6)-linked β-d-Gal. The branches of FCPW80-2 consist of (1→4)-linked α-d-Glc and (1→3)-linked β-l-Rha terminated with (1→)-linked β-d-Glc. In v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 42 publications
4
39
0
Order By: Relevance
“…These results of the present study were in agreement with the studies on hetero-galacturonans obtained from sweet cherry and stem lettuce [10,11]. Therefore, these results suggested that PFP2, PFP3, and PFP4 may play an immunomodulatory role through promoting the secretion of TNF-α, IL-6, and NO in RAW264.7 macrophages, which are essential for killing pathogens, microorganisms, and coordinating various biological activities as intracellular messenger molecules [5].…”
Section: Immunomodulatory Effectsupporting
confidence: 92%
See 1 more Smart Citation
“…These results of the present study were in agreement with the studies on hetero-galacturonans obtained from sweet cherry and stem lettuce [10,11]. Therefore, these results suggested that PFP2, PFP3, and PFP4 may play an immunomodulatory role through promoting the secretion of TNF-α, IL-6, and NO in RAW264.7 macrophages, which are essential for killing pathogens, microorganisms, and coordinating various biological activities as intracellular messenger molecules [5].…”
Section: Immunomodulatory Effectsupporting
confidence: 92%
“…Among the salt-eluted polysaccharides, such as galactans, glucans, galacturonans, galacturonans have attracted more attention in modern pharmacology [5][6][7]. It is one kind of polysaccharides with a backbone of galactopyranouronic (GalpAc) residues and mostly distributed in plants as heterozygotes, which have extensively gained concerns because of their multiple biological properties, especially the immunomodulatory activities [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…We followed the methods described in Juan Du et al [53] to measure the proteins levels of iNOS, IκB-α, NF-κB and NLRP3 using western blotting. Total protein of the treated cells was extracted using RIPA lysis buffer, and protein concentration was measured using a bicinchoninic acid (BCA) protein quantification kit (Solarbio, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Polysaccharide is a component of biological organisms and an important biologically active substance that possesses multiple functions, such as antioxidant (Dammak et al, ; Ji et al, ; Ye et al, ), anti‐obesity (Chang et al, ) and immunomodulating properties (Du J et al, ; Jin et al, ; Yu et al, ). The human body lacks carbohydrate active enzymes that can utilize polysaccharides directly.…”
Section: Introductionmentioning
confidence: 99%